Calculation of reserve estimation in the new pit design using mining software at PT. Tanjung Alam Jaya pit x, Banjar, South Borneo. - Muhammad Faris Akbar; Abimanyu Mahardhika; Avellyn Shinthya Sari (Journal of Earth and Marine Technology (JEMT), 2023)
The mining planning and design were carried out in PT. Tanjung Alam Jaya, a coal mining company in South Kalimantan. The company intends to re-mine the Pit X area and requires a comprehensive mine planning approach to achieve its mining objectives. The study focuses on long-term planning, specifically optimizing the pit design while considering the company's specified stripping ratio limit and calculating the potential reserve volumes. The research aims to develop an optimized pit design and estimate the quantity of mineable reserves based on the optimization results. The findings include a mining layout design drawing and the calculated coal reserves that can be extracted from the optimized pit design. The excavation area spans 38.1 hectares, with excavation limits reaching a depth of -56 meters above sea level. The shape of the excavation extends from northeast to southwest, with a length of 1,065 meters and a variable width of 310 to 460 meters. The excavation features a slope height of 10 meters and a single slope angle of 65 degrees. Moreover, the haul road measures 21 meters in width with a 10% grade. The pit design indicates a total mineable coal reserve of 1,400,263.48 tons across all seams. Additionally, it reveals that 21,565,312.42 bcm of overburden / interburden must be stripped, resulting in a stripping ratio of 15.40 for the specific pit design. The haul road measures 21 meters in width with a 10% grade. In conclusion, this research demonstrates PT Tanjung Alam Jaya's efforts to optimize their pit design for re-mining in the Pit X area. The study provides valuable insights through a comprehensive mine planning approach, aiding the company in achieving their mining objectives while adhering to specified limits.